Environmental History Transcending Boundaries: Colonial to Contemporary India - Kumar, Varun (IISER-M, 2016)
Environmental history is a relatively recent field which emerged from popular resistance movements against environmental degradation in the 1970s. The dominant theme in environmental history writing is of defending nature against exploitation from humans. India’s environmental history is periodized into: pre-colonial, colonial and post-colonial periods. Pre-colonial past is often portrayed as a harmonious tale with nature and humans coexisting. Against this static background, colonial past is viewed as having very violent consequences for the environment. The post-colonial state policies regarding environment have also received less attention compared to colonial past. It is true that policies of British had enormous consequences for India’s environment and some of the policies introduced had no precedence in history but there are some continuities which exist between colonial and post-colonial state. In my work, I have looked at certain narratives which extend beyond the periodization and lay emphasis on the continuities which exist. I have mainly looked at colonial state policies regarding wildlife and forests with some focus on irrigation policies and British attitude towards science in India.
Keywords: Social Science; History; India